Isolated Intracranial Rosai Dorfman Disease: A Rare Presentation with Diagnostic Mimickers - Singh, Ritika; Shah, Milap; Balasubramaniam, Anandh; Rajesh, B J (Annals of Pathology and Laboratory Medicine, 2020)
Rosai-Dorfman Disease (RDD) is an idiopathic lymphohisticyocytic disorder characterized clinically by massive painless cervical lymphadenopathy, fever and weight loss. Extranodal involvement has been recognized. Central nervous system (CNS) manifestations are rare. Intracranial localization of the disease without involvement of other sites is very rare and needs to be differentiated from various mimicking lesions especially meningioma. A radiological and histological confirmation followed by complete resection of the lesion is the treatment of choice.